Desensitizing Addiction: Using Eye Movements to Reduce the Intensity of Substance-Related Mental Imagery and Craving - Littel, Marianne; van den Hout, Marcel A.; Engelhard, Iris M. (Frontiers in Psychiatry, 2016)
Eye movement desensitization and reprocessing (EMDR) is an effective treatment for posttraumatic stress disorder. During this treatment, patients recall a traumatic memory while making horizontal eye movements (EM). Studies have shown that EM not only desensitize negative memories, but also positive memories and imagined events. Substance use behavior and craving are maintained by maladaptive memory associations and visual imagery. Preliminary findings have indicated that these mental images can be desensitized by EMDR techniques. We conducted two proof-of-principle studies to investigate whether EM can reduce the sensory richness of substance-related mental representations and accompanying craving levels. We investigated the effects of EM on 1) vividness of food-related mental imagery and food craving in dieting and non-dieting students, and 2) vividness of recent smoking-related memories and cigarette craving in daily smokers. In both experiments, participants recalled the images while making EM or keeping eyes stationary. Image vividness and emotionality, image-specific craving and general craving were measured before and after the intervention. As a behavioral outcome measure, participants in study 1 were offered a snack choice at the end of the experiment. Results of both experiments showed that image vividness and craving increased in the control condition, but remained stable or decreased after the EM intervention. EM additionally reduced image emotionality (exp 2), and affected behavior (exp 1): participants in the EM condition were more inclined to choose healthy over unhealthy snack options. In conclusion, the data suggest that EM can be used to reduce intensity of substance related imagery and craving. Although long-term effects are yet to be demonstrated, the current studies suggest that EM might be a useful technique in addiction treatment.